2015
DOI: 10.1002/jmv.24155
|View full text |Cite
|
Sign up to set email alerts
|

Four-year study of viruses that cause diarrhea in Japanese pediatric outpatients

Abstract: Acute gastroenteritis continues to be a major public health problem worldwide. A wide variety of viruses associated with diarrhea disease is being reported continually. This study investigated the epidemiological situation of viruses that cause diarrhea in Japanese pediatric patients. This study enrolled a total of 2,381 fecal specimens collected between 2009 and 2013 from Japanese children with acute gastroenteritis. There is currently a 70.4% prevalence of viruses causing diarrhea among these Japanese pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
72
5
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 48 publications
14
72
5
1
Order By: Relevance
“…This finding was supported by several recent reports, in which sapovirus was detected more commonly in symptomatic children aged 12 to 23 months than in those aged Ͻ1 year (9,21,35,36). Lower detection rates of sapovirus in children aged Ͻ1 year possibly reflect a protective effect of breastfeeding and/or transferred maternal antibodies (22,37), as supported by the fact that we did not detect sapovirus in symptomatic children under 6 months.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was supported by several recent reports, in which sapovirus was detected more commonly in symptomatic children aged 12 to 23 months than in those aged Ͻ1 year (9,21,35,36). Lower detection rates of sapovirus in children aged Ͻ1 year possibly reflect a protective effect of breastfeeding and/or transferred maternal antibodies (22,37), as supported by the fact that we did not detect sapovirus in symptomatic children under 6 months.…”
Section: Discussionsupporting
confidence: 91%
“…NoV is the well recognized viral pathogen which causes epidemic and sporadic diarrhea in both adults and children. Some studies have even reported it as the leading cause of diarrhea, especially in children where rotavirus is believed to be the foremost viral pathogen [35]. Among various NoV genogroups, the outcome of majority of the studies shows that GII is the foremost cause of diarrhea in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The role of viral pathogens in diarrhea is well established and several diarrheagenic viruses have been reported till date [7,38]. The disease burden associated with the viral gastroenteritis has been well documented in the studies from all over the world [30,35]. Rotavirus (RV), the RNA (segmented double stranded) virus belonging to the family of Reoviridae is the major viral agent which is responsible for diarrhea basically in children below the age group of 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Norovirus was predominantly detected (39.3 %), whereas the prevalence of rotavirus, human parechovirus, enterovirus, and adenovirus was 20.1, 6.6, 6.1, and 5.6 %, respectively [9]. The molecular epidemiology of norovirus genotypes in this population were also analyzed by Thongprachum et al [10].…”
Section: Discussionmentioning
confidence: 97%
“…From 2009 to 2013, the incidence of viral acute gastroenteritis among 2,381 Japanese pediatric patients was examined by Thongprachum et al [9]. Norovirus was predominantly detected (39.3 %), whereas the prevalence of rotavirus, human parechovirus, enterovirus, and adenovirus was 20.1, 6.6, 6.1, and 5.6 %, respectively [9].…”
Section: Discussionmentioning
confidence: 99%